Fishing boats at anchor at Morro Bay, California. - Albert Walton DeRome:::Creator::::::::::::
Various large purse seiners and non-fishing boats at anchor at low tide at Morro Bay, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.)